POLA KOMUNIKASI INTRABUDAYA SISTEM KEKERABATAN DALAM MEMELIHARA FALSAFAH HIDUP DALIHAN NA TOLU (Studi Pada Masyaraka Batak di Desa Bukit Gajah kecamatanUkui) - Hasanah, Miladiatul; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Batak society is one of the people who have a lot of uniqueness starting from the language, marriage system, kinship system and philosophy of life that they hold high Dalihan Na Tolu. Batak society we encountered many in various places in Indonesia is no exception in Bukit Gajah Village is one of the existing village in Ukui District. Batak community will always maintain and preserve their cultural customs even though they are far away in overseas especially kinship system. In every interaction done Batak society will still use their life philosophy that is Dalihan Na Tolu. For the people of Batak Dalihan Na Tolu is a philosophy of life that will never be abandoned until whenever. Based on the background there is a question that is how the Batak people who are in the overseas especially in the Village of Mount Gajah. The method used in this research is descriptive qualitative method with the theory of symbolic interaction. Data collected through interviews, observation and documentation. Informants in this study amounted to eight people determined by purposive sampling technique. The results of research in maintaining the philosophy of na tolu transition that is always upheld although overseas, in the process of communication Batak community in Bukit Gajah Village still based on the dalihan na tolu and also when carrying out the ceremony there is a wedding. Furthermore, in maintaining the transition na tolu they do intrabudaya communication pattern that is interpersonal and group communication. Keywords: na tolu transfers, intracultural communication patterns, Batak society.